Analytical model for total ionizing dose-induced excess base current in PNP BJTs. (October 2020) - Li, L.; Chen, X.C.; Li, X.J.; Li, Z.H.; Jian, Y.; Wu, Y.Z.; Zhang, J.P.; Ren, M.; Zhang, B.
Abstract: This work analytically models the crucial physical mechanisms accountable for the defect kinetics and the degradation of base current in PNP BJTs. Both the space charge and bimolecular mechanisms have been incorporated to elicit the defect dynamics (oxide charge and interface trap) following ionization radiation. Thereafter, two novel insights into the ionization damage on SiO2 of bipolar structure are provided, which includes the coupled effect of the two defect mechanisms and the existence of an "additional" hydrogen sensitivity in the bimolecular mechanism. A previous device model has been updated to describe the response of base current degradation to defects build-up. Further, a closed-form compact expression for the excess base current is provided, which is an explicit function of the total ionizing dose, dose rate, and hydrogen concentration. The new model closely fits the experimental data from several devices, including RF25 capacitor, gate controlled lateral PNP BJT, and LM124 amplifier. Our model delivers a practical approach to deduct the oxide charge modulation effect on excess base current. Thereafter, the relation between the modified excess base current and total ionizing dose is linear. Furthermore, this work suggests a practical approach, called as "offset current approach", to predict the excess base in PNP BJTs at low dose rate. Highlights: Provides a closed-form compact analytic expression for the excess base current as an explicit function of irradiation dose. Both "effective holes yield model" and "bimolecular model" are combined to discuss the ELDRS. It shows the log-log slope of the plot of excess base current versus dose being constant in certain dose regions. The model suggests a novel accelerated approach for ELDRS of BJTs. We report the experiments results of LM124 operation amplifier at ultra low dose rate.